Assessment of the progress of the therapy by the FED in patients with scoliosis idiopathic - Rychter, Paweł; Paprocki, Michał Jerzy; Wilczyński, Igor; Wilczyńska, Katarzyna; Wilczyński, Jacek (Journal of Education, Health and Sport, 2017)
Summarizing the result of x-rays and Diers Formetric III 4 D, it can be concluded that the girl received improved on as a result of the treatment method of F.E.D.. The angle of the original curvature was 56 ° in the thoracic region and 50 ° in the lumbar region measured by Cobb. After corrections were obtained curvature of the spine, which respectively in the thoracic region 46 °, and 45 ° lumbar. In addition, the method of opto-Diers Formetric III 4 D allows a constant control and evaluation of the progress of the therapy method F.E.D. is completely devoid of harmful x-rays. By comparing the results of the angles in the curve and the degree of rotation in all of the studies, it can be concluded that the results represent a significant correction of spine patients. In addition, was a link between the tests and X-RAY Diers Formetric 4 D. Angles in the curve in both studies were situated within the limits of the measurement errors which proves their correlation. So far, however, no studies have been conducted on a large research group in order to prove the direct correlation between the two diagnostic methods. This system can be presented to the various clinical issues an objective and quantitative analysis of body posture and scoliosis. This is currently the most modern non-invasive evaluation system.